Chapter 3 - Strategies to reduce lipid consumption - Marszałek, Krystian (2020)
Lipids are macronutrients that have important functions in the body like storing energy, signaling, and acting as structural components in cell membranes. However, the daily consumption of a high-lipid diet has been involved in the development and maintenance of obesity, a disease which its prevalence is increasing globally. Because of that, the food industry is working in strategies to develop new food products with the aim of reducing the lipid intake. Among these strategies are (1) changes in the structural design of food, (2) the use of carbohydrate and/or fat substitutes, and (3) the inhibition of enzymes responsible for the digestion of sugars and/or lipids. These strategies will be described in the chapter in order to show the advances in food technology to achieve the reduction of lipid content in food products.